IMPLEMENTATION OF DIGITAL LITERACY MOVEMENT FOR MSMEs ACTORS IN JAKARTA THROUGH PARTICIPATORY ACTION RESEARCH - Rialdo Rezeky Manogari L. Toruan; Radja Erland Hamzah; Muhammad Saifulloh (Universitas prof. Dr. Moestopo (Beragama), 2021)
Digital literacy is an interesting study at this time in the midst of the development of Information and Communication Technology (ICT), especially for SMEs. Through socialization and digital literacy training, MSME actors can apply in their business so that they are skilled and can market their products as well as increase income and improve the economy. The purpose of this study is to identify the actions of MSME actors in Kuningan Barat, South Jakarta. The research approach is qualitative and the method used is Stephen Kemmis's Action Research (PRA), and the concept used is the digital literacy stage of Steve Wheeler. The results show that digital literacy can be implemented through socialization and training that is realized in a digital product. Through action participation, MSME actors can be digitally literate and use digital media well. In this case, MSME actors create a website product www.plazakuninganbarat.com as a medium for digital marketing.